2021
DOI: 10.24191/ajue.v16i4.11952
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Educational Practice for Impactful Teaching Strategies through Scaffolding Method

Abstract: As technology progresses in education, 21st-century educators need to use impactful instructional methods to ensure that the focus of education is on preparing today's children for the future. However, the biggest challenge for most lecturers in Multimedia University is teaching the non-graded subjects (pass or fail in nature). Since the subjects do not affect the CGPA, students were found not being serious or showing interest in the class. Consequently, it affects the learning outcome of the subject and also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
1
0
Order By: Relevance
“…What's interesting about the findings in this study is that the factors that influence teachers' self-efficacy correlate with their previous teaching experience, the pedagogical training they have attended, the perceived support from colleagues, and personal efficacy beliefs. Some previous research has also found that teachers' self-efficacy in instructional strategies positively impacts student outcomes (Jerez et al, 2021;Rahmat et al, 2020). When teachers believe in their ability to use effective teaching methods, students tend to perform better academically.…”
Section: Indonesian Efl Teachers' Self-efficacy Beliefsmentioning
confidence: 97%
“…What's interesting about the findings in this study is that the factors that influence teachers' self-efficacy correlate with their previous teaching experience, the pedagogical training they have attended, the perceived support from colleagues, and personal efficacy beliefs. Some previous research has also found that teachers' self-efficacy in instructional strategies positively impacts student outcomes (Jerez et al, 2021;Rahmat et al, 2020). When teachers believe in their ability to use effective teaching methods, students tend to perform better academically.…”
Section: Indonesian Efl Teachers' Self-efficacy Beliefsmentioning
confidence: 97%
“…In language, fiqh is understanding, while in terms, fiqh is knowledge of shari'a law obtained from detailed arguments (Sukumar, 2021). In learning, fiqh can be taught from various da'wah with lectures from ustadz and ustadzah accompanied by certain practices in order to understanding of the practice of fiqh itself (Rahmat, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Teachers associate methodological development of lessons mainly with the structuring of educational material and description of the sequence. Simultaneously, the logic of conducting classes should correspond to the logic of students' assimilation of academic subjects' material, the formation of skills and abilities, motivation and stimulation of learning, and other components of the pedagogical process (Afanasiyivna, 2017;Rahmat et al, 2021).…”
Section: Introductionmentioning
confidence: 99%